Structural basis for endoperoxide-forming oxygenases - Mori, Takahiro; Abe, Ikuro (Beilstein Journal of Organic Chemistry, 2022)
Endoperoxide natural products are widely distributed in nature and exhibit various biological activities. Due to their chemical features, endoperoxide and endoperoxide-derived secondary metabolites have attracted keen attention in the field of natural products and organic synthesis. In this review, we summarize the structural analyses, mechanistic investigations, and proposed reaction mechanisms of endoperoxide-forming oxygenases, including cyclooxygenase, fumitremorgin B endoperoxidase (FtmOx1), and the asnovolin A endoperoxygenase NvfI.
Keywords: biosynthesis; endoperoxide; enzyme; natural products; X-ray crystallography